PENGARUH=DEBT TO EQUITY RATIO DAN-NET/PROFIT MARGIN-TERHADAP HARGA SAHAM/PERUSAHAAN OTOMOTIF YANG-TERDAFTAR-DI BEI TAHUN 2014 – 2021 - Novita Ika Dyamayanti; Renea Shinta Aminda; Diah Yudhawati (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Stock price valuation is an investment valuation that is often used by investors to invest because of the many advantages. This research uses quantitative research methods. This research-was conducted to-determine theeffect-of Debt To Equity-Ratio andNet Profit Margin on stock prices. The population in this study were 16 automotive companies listed on the IDX in 2014 – 2021. The research sample used a purposive sampling method to produce 11 suitable companies. The analysis used is-descriptive analysis-and multiple linear analysis. Based on simultaneous testing, it is known thatthe Debt to Equity Ratio and Net Profit-Margin variables simultaneously affect stock prices. While the results of the partial test of the Debt To Equity Ratio variable have-a positive effect onstock prices, while the Net Profit-Margin variable-has no effect onstock prices.